Cryptanalysis and Secure Redesign of a Fog-Based Mutual Authentication Protocol for the Social Internet of Vehicles - Swasti Jain; Akash Kumar; Saru Kumari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Li et al. proposed a provably secure and lightweight mutual authentication protocol for fog-enabled Social Internet of Vehicles, claiming resistance to various attacks, including offline password guessing and insider threats. However, upon thorough analysis, we identified several vulnerabilities in their scheme, such as susceptibility to insider attacks and offline password guessing. In response, we present a set of recommendations aimed at strengthening the protocol and addressing the identified weaknesses.
Keywords: Social Internet of vehicles; Authentication; Fog-Enabled Networks